Inhibiting nuclear factor erythroid 2 related factor 2-mediated autophagy in bovine mammary epithelial cells induces oxidative stress in response to exogenous fatty acids - Chang, Renxu; Sun, Xudong; Jia, Hongdou; Xu, Qiushi; Dong, Zhihao; Tang, Yan; Luo, Shengbin; Jiang, Qianming; Loor, Juan J.; Xu, Chuang (Journal of animal science and biotechnology, 2022)
In early lactation, bovine mammary epithelial cells undergo serious metabolic challenges and oxidative stress both of which could be alleviated by activation of autophagy. Nuclear factor erythroid 2 related factor 2 (NFE2L2), a master regulator of cellular redox homeostasis, plays an important role in the regulation of autophagy and oxidative stress. Thus, the objective of this study was to investigate the role of NFE2L2-mediated autophagy on oxidative stress of bovine mammary epithelial cells in response to exogenous free fatty acids (FFA). Exogenous FFA induced linear and quadratic decreases in activities of glutathione peroxidase (GSH-Px), catalase (CAT), and superoxide dismutase (SOD), and increases in the contents of reactive oxygen species (ROS) and malondialdehyde (MDA). Protein abundance of LC3-phosphatidylethanolamine conjugate (LC3-II) and the number of autophagosomes and autolysosomes decreased in a dose-dependent manner, while protein abundance of p62 increased in cells challenged with FFA. Activation of autophagy via pre-treatment with Rap attenuated the FFA-induced ROS accumulation. Importantly, FFA inhibited protein abundance of NFE2L2 and the translocation of NFE2L2 into the nucleus. Knockdown of NFE2L2 by siRNA decreased protein abundance of LC3-II, while it increased protein abundance of p62. Furthermore, sulforaphane (SFN) pre-treatment attenuated the FFA-induced oxidative stress by activating NFE2L2-mediated autophagy. The data suggested that NFE2L2-mediated autophagy is an important antioxidant mechanism in bovine mammary epithelial cells experiencing increased FFA loads.